THE EFFECT OF PRICE, LOCATION, LAYOUT, PROMOTION AND PRODUCT QUALITY ON BUSINESS GROWTH - Sarwo Edy; Sukron Mamun (Jurnal Ekonomi, 2022)
This study aims to determine the influence partially and simultaneously of variable prices, locations, layouts, promotions and product quality on the growth of the cikarang Bekasi baby supplies store business. The research method used in this study is to use quantitative research methods. The sampling used in this study was using the Probability Sampling method and the type of sampling using simple random sampling. The total population of 160 respondents then used the slovin formula to get the sample studied as many as 106 respondents. The analytical methods used are validity test, reability test, classical assumption test, hypothesis test and multiple linear analysis assisted by using IBM SPSS 25. The results showed that the variables of price, layout and product quality partially had a positive and significant effect on purchasing decisions. Location variables and partial promotions have no effect on business growth.